2012
DOI: 10.1016/j.freeradbiomed.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 2 decreases renal reactive oxygen species production, lowers blood pressure, and mediates dopamine D2 receptor-induced inhibition of NADPH oxidase

Abstract: The dopamine D2 receptor (D2R) regulates renal reactive oxygen species (ROS) production and impaired D2R function results in ROS-dependent hypertension. Paraoxonase 2 (PON2), which belongs to the paraoxonase gene family, is expressed in various tissues, acting to protect against cellular oxidative stress. We hypothesized that PON2 may be involved in preventing excessive renal ROS production and thus may contribute to maintenance of normal blood pressure. Moreover, the D2R may decrease ROS production, in part, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 48 publications
(70 reference statements)
5
80
0
Order By: Relevance
“…Previous studies from our laboratory have shown that disruption of Drd2 (D 2 R −/− ) increases systolic and diastolic blood pressures that are associated with increased ROS production and oxidative stress in the kidney [12, 15, 26, 27]. To determine if sestrin2 is involved in these alterations, we first measured the renal protein expression of sestrin2 in D 2 R −/− and D 2 R +/+ mice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies from our laboratory have shown that disruption of Drd2 (D 2 R −/− ) increases systolic and diastolic blood pressures that are associated with increased ROS production and oxidative stress in the kidney [12, 15, 26, 27]. To determine if sestrin2 is involved in these alterations, we first measured the renal protein expression of sestrin2 in D 2 R −/− and D 2 R +/+ mice.…”
Section: Resultsmentioning
confidence: 99%
“…The D 2 R decreases cellular oxidative stress in human RPTCs [15]. To determine whether or not sestrin2 is involved in the anti-oxidant effect of D 2 R, we treated human RPTCs with the D 2 R agonist quinpirole in the presence of siRNA targeting human sestrin2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PON gene family consisting of at least 3 genes (PON1, PON2 and PON3) located in the long arm of human chromosome 7 (q21.3-22.1) coding for esterases (19). PON2 expressing in tissues throughout the body may develop its antioxidant effect at a cellular level (20), and its deficiency can increase ROS production, which led to the damage of cochlear hair cell (21). Some researchers have found that PON2 polymorphisms may be associated with diseases, such as ischemic stroke, diabetes, and Alzheimer's dementia (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%